O canto coral no ensino fundamental: Algumas práticas e texturas polifônicas como proposta de musicalização - BELAGLOVIS, Ivonilde Pereira Coelho (2023)
This research aims to investigate elements that characterize and justify the use of arrangements for choral singing in elementary school, using some polyphonic textures to develop awareness of the constituent parts of music: the rhythmical, melodical and harmonical one, through singing. As a methodological contribution that is best suitable to this study, is presented an exploratory research, with a qualitative approach and case study, and the instruments and techniques used for this study were collected through primary sources, through participant observation, where, As a result, we obtained the recording of original vocal arrangements of Brazilian folk songs collected by Villa-Lobos, Tavinho Moura and Ermelinda Azevedo Paz. Semi-structured questionnaires were also used as a form of data collection, elaborated with mixed questions, constructed according to the specific objectives of this research and applied to students enrolled in the Escola Municipal de Música de São Luís (EMMUS). Data analysis was presented using the descriptive analysis technique. The realization of this research aimed mainly, in addition to the possibility of contributing to the improvement of musical-pedagogical practice in elementary school, to collaborate in the formation of students more participative and motivated in music classes, stimulating musical perception through songs of Brazilian folklore, in search of an artistic experience of better quality to offer the students in this stage of teaching. This work reached as conclusion that the polyphonic textures applied to choral singing at school contributed to the development of students' musical perception in elementary school.